The influence of rurality and its indigenous knowledge on teaching methods in higher education - lessons from Ukulange Mbusa of the Bemba people of Zambia - Dennis Banda; Mulenga Kapwepwe (University of Johannesburg, 2020)
This study was on the influence of rurality and its Indigenous Knowledge Systems (IKS) with reference to the Ukulange Mbusa (UM) ceremony of the Bemba people of the Northern Zambia. Rurality is a demographic and a social category and implies distance from urban centres, sparse population, lack of amenities, infrastructure and sometimes social deprivation. A lot of forms of indigenous knowledge are imparted on learners from rural areas before they join universities and meet other knowledge systems. The study tried to establish if some learning and teaching approaches, methods and techniques used in such traditional ceremonies and settings could influence the teaching and learning in higher learning institutions. Interviews, Focus Group Discussions (FGD), and documents analysis were used to collect data. The sample was drawn from traditional chiefs, women counsellors (alangizi) and university students initiated in the Ukulange Mbusa ceremony. Findings of the study are that the positive influences of rurality and their forms of indigenous knowledge are often minimised, misunderstood, ignored, viewed as backward, local, native, and therefore not suitable for use in higher learning institutions. However, this study argues that progressive indigenous forms of knowledge must be hybridized with the university ones, save negative ones such as those fuelling early marriages. Keywords: Indigenous knowledge, Rurality, Folklore, Culture, Zambia How to cite this article: Banda, D. & Kapwepwe, M. 2020. The influence of rurality and its indigenous knowledge on teaching methods in higher education - lessons from Ukulange Mbusa of the Bemba people of Zambia. Scholarship of Teaching and Learning in the South. 4(2): 197-217. https://doi.org/10.36615/sotls.v4i2.148. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/